A Couples-Oriented Intervention for Positive Airway Pressure Therapy Adherence: A Pilot Study of Obstructive Sleep Apnea Patients and Their Partners. Issue 5 (3rd September 2019) - Luyster, Faith S.; Aloia, Mark S.; Buysse, Daniel J.; Dunbar-Jacob, Jacqueline; Martire, Lynn M.; Sereika, Susan M.; Strollo, Patrick J.
ABSTRACT: Background : Partner involvement can influence positive airway pressure (PAP) therapy use among patients with obstructive sleep apnea (OSA). This study assessed the feasibility, acceptability, and preliminary efficacy of a couples-oriented education and support (CES) intervention for PAP adherence. Participants : Thirty newly diagnosed OSA patients and their partners were randomly assigned to one of three groups: an education and support intervention directed at both patient and partner (CES), an education and support intervention directed only at the patient (PES), or usual care (UC). Methods : Feasibility and acceptability were assessed through enrollment and posttreatment program evaluations, respectively. Assessments of sleep quality, daytime sleepiness, and daytime function were obtained from both patients and partners at baseline and 3 months after PAP initiation. Objective PAP adherence was assessed at 1 week, 1 month, and 3 months. Results : Recruitment and attrition data suggest adequate feasibility. All patients and partners in the CES group reported that the intervention was helpful. Patients in the CES and PES groups increased their PAP adherence over the first month of treatment, whereas PAP adherence decreased over this period in the UC group. For patients, large to medium effects for sleep quality ( d  = −1.01), daytime sleepiness ( d  = −0.51), and daytime function ( d  = 0.51) were found for the CES group. The PES and UC groups effect sizes were large to small for sleep quality ( d  = −0.94; d  = −0.40), daytime sleepiness ( d  = −0.42; d  = −0.82), and daytime function ( d  = 0.41; d  = 0.57), respectively. For partners, large effects for daytime sleepiness ( d  = −1.31) and daytime function ( d  = 1.54) and small to medium effect for sleep quality ( d  = −0.31) were found for the CES group. Worsening of sleep quality ( d  = 0.65) and no change in daytime sleepiness or daytime function were found for the PES group. For the UC group, medium to large effects were found for sleep quality ( d  = −0.77), daytime sleepiness ( d  = −0.77), and daytime function ( d  = 0.65). Conclusions : The findings of this pilot study provide support for taking a couples intervention approach to improve PAP adherence.